Perspectives of Patients in Identifying Their Values‐Based Health Priorities. Issue 7 (7th March 2019) - Feder, Shelli L.; Kiwak, Eliza; Costello, Darcé; Dindo, Lilian; Hernandez‐Bigos, Kizzy; Vo, Lauren; Geda, Mary; Blaum, Caroline; Tinetti, Mary E.; Naik, Aanand D.
Abstract : OBJECTIVES: Patient Health Priorities Identification (PHPI) is a values‐based process in which trained facilitators assist older adults with multiple chronic conditions identify their health priorities. The purpose of this study was to evaluate patients' perceptions of PHPI. DESIGN: Qualitative study using thematic analysis. SETTING: In‐depth semistructured telephone and in‐person interviews. PARTICIPANTS: Twenty‐two older adults who participated in the PHPI process. MEASUREMENTS: Open‐ended questions about patient perceptions of the PHPI process, perceived benefits of the process, enablers and barriers to PHPI, and recommendations for process enhancement. RESULTS: Patient interviews ranged from 9 to 63 minutes (median = 20 min; interquartile range = 15–26). The mean age was 80 years (standard deviation = 7.96), 64% were female, and all patients identified themselves as white. Of the sample, 73% reported no caregiver involvement in their healthcare; 36% lived alone. Most patients felt able to complete the PHPI process with ease. Perceived benefits included increased knowledge and insight into disease processes and treatment options, patient activation, and enhanced communication with family and clinicians. Patients identified several factors that were both enablers and barriers to PHPI including facilitator characteristics, patient demographic and clinical characteristics, social support, relationships between the patient and their primary care provider, and the changing health priorities of the patient. Recommendations for process enhancement included more frequent and flexible facilitator contacts, selection of patients for participation based on specific patient characteristics, clarification of process aims and expectations, involvement of family, written reminders of established health priorities, short duration between facilitation and primary care provider follow‐up, and the inclusion of health‐related tasks in facilitation visits. CONCLUSIONS: Patients found the PHPI process valuable in identifying actionable health priorities and healthcare goals leading to enhanced knowledge, activation, and communication regarding their treatment options and preferences. PHPI may be useful for aligning the healthcare that patients receive with their values‐based priorities.